2019
DOI: 10.17221/71/2018-swr
|View full text |Cite
|
Sign up to set email alerts
|

Carbon pool in soil under organic and conventional farming systems

Abstract: Changes in the agricultural management and climatic changes within the past 25 years have had a serious impact on soil organic matter content and contribute to different carbon storage in the soil. Prediction of soil carbon pool, validation, and quantification of different models is important for sustainable agriculture in the future and for this purpose a long-term monitoring data set is required. RothC-26.3 model was applied for carbon stock simulation within two different climatic scenarios (hot-dry with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Another well-known model is the EPIC model, which is a process-based model describing the interactions between the climate and soil [37,38]. The model RothC-26.3 is focused on the turnover of organic C in non-waterlogged soils that allow analysing the effects of soil type, temperature, moisture content and plant cover on the turnover process [39,40]. There were also developed many other models [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Another well-known model is the EPIC model, which is a process-based model describing the interactions between the climate and soil [37,38]. The model RothC-26.3 is focused on the turnover of organic C in non-waterlogged soils that allow analysing the effects of soil type, temperature, moisture content and plant cover on the turnover process [39,40]. There were also developed many other models [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…In assessing the SOC content under shallow ploughless tillage with additional deep loosening and shallow ploughless tillage, the SOC content was similar. These data suggest that there was a positive effect of reduced tillage on SOC accumulation in upper soil layers due to low soil disturbance and slow decomposition of surface-placed plant residues, which has been established in several experiments carried out in temperate climate conditions [53,54]; however, several studies have shown that tillage has an insignificant effect on SOC content, though can change the distribution of SOC in soil profile.…”
Section: Carbon Stock In the Soil Under Different Combination Of Tillage And Organic Fertilizationmentioning
confidence: 62%
“…Finally, it should be emphasized that organic farming is not necessarily synonymous with "protection of the carbon present in the soil". In fact, if carbon inputs are insufficient to maintain the carbon balance in the soil, the soil is depleted [53,54]. However, some agronomic practices typical of organic management (e.g., cover crops, minimum tillage, and organic fertilization) generally lead to a lower risk of SOC depletion, in comparison to conventional management.…”
Section: Relevance Of Soil Carbon Storage In Terms Of Co 2 Equivalentmentioning
confidence: 99%
“…The cover crops choice (e.g., choosing field beans over grassland) is one of the main critical factors. Nevertheless, Hábová et al [53] stated that in spite of less carbon input, organic farming was more stable in comparison to intensive farming. The intensive farming system was much more affected by climatic condition and plant residues input.…”
Section: Suggestions From the Rothc Model To Improve The Farm Environ...mentioning
confidence: 99%